2018
DOI: 10.3390/polym10030316
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ex Vivo Transmucosal Permeation of Pioglitazone Nanoparticles for the Treatment of Alzheimer’s Disease

Abstract: Pioglitazone has been reported in the literature to have a substantial role in the improvement of overall cognition in a mouse model. With this in mind, the aim of this study was to determine the most efficacious route for the administration of Pioglitazone nanoparticles (PGZ-NPs) in order to promote drug delivery to the brain for the treatment of Alzheimer’s disease. PGZ-loaded NPs were developed by the solvent displacement method. Parameters such as mean size, polydispersity index, zeta potential, encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Moreover, the theoretical human steady-state plasma concentration ( C ss ) of drug, which estimates the concentration of drug that could be reached in the blood after nasal administration, was obtained using Equation (2). Css=Jss AClp where J ss is the flux, A is the hypothetical area of application (150 cm 2 for nasal mucosa), and Clp is the plasmatic clearance (human Clp value for DPZ according to the Food and Drug Administration is 10 L/h) [28].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the theoretical human steady-state plasma concentration ( C ss ) of drug, which estimates the concentration of drug that could be reached in the blood after nasal administration, was obtained using Equation (2). Css=Jss AClp where J ss is the flux, A is the hypothetical area of application (150 cm 2 for nasal mucosa), and Clp is the plasmatic clearance (human Clp value for DPZ according to the Food and Drug Administration is 10 L/h) [28].…”
Section: Methodsmentioning
confidence: 99%
“…Parameters such as size, polydispersity index (PDI) and Zeta Potential (ZP) were evaluated to confirm the stability with a Zetasizer Nano ZS (Malvern Instruments, Malvern, UK). Additionally, the encapsulation efficiency (EE) was determined by the indirect method [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The new formulations improved the biopharmaceutical profile of the drugs. In particular, PGZ-NPs of PLGA-PEG were formulated for eye treatment and also for delivery to the brain [ 12 , 47 ]. These nanosystems were optimized, characterized, and their anti-inflammatory activity, as well as their tolerance, were demonstrated for in vitro, ex vivo, and in vivo animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PGZ was encapsulated into PLGA-PEG-NPs, suggesting its suitability as a pharmaceutical formulation that overcomes the poor solubility of PGZ in an aqueous phase [54] and targets specific tissues [46,55,56]. Moreover, this system showed good corneal and scleral permeation and sustained release, indicating these systems could be useful for drug delivery [52].…”
Section: Introductionmentioning
confidence: 99%